Realizations : Narrative, Pictorial, and Theatrical Arts in Nineteenth-Century England. - Meisel, Martin (Princeton legacy library., 2014)
In this richly illustrated study of the relationship of art, drama, and fiction in the nineteenth century, Martin Meisel illuminates the collaboration between storytelling and picturemaking that informed narrative painting, pictorial dramaturgy, and serial illustrated fiction. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books whi.